International standards in the field of media (International relations and international law Journal, 2016)
In this articlewere considered the international cooperations in field of the use of mass media. Author tried to make international legal norm governing the activities of the media.Theinternational cooperation in the field of media associated with the problems of technical conditions, of international exchange of information, ofinformation content. Particular attention is paid to international – legal regulation of these issues, as well as the legal regulation of freedom of speech in Kazakhstan This article covered legal documents authorizing problems of mass-media between the countries.
Keywords: mass-media; international cooperation; international standards; freedom of speech; information